Ion Channel Dysfunction and Neuroinflammation in Migraine and Depression - Eren-Koçak, Emine; Dalkara, Turgay (Frontiers in Pharmacology, 2021)
Migraine and major depression are debilitating disorders with high lifetime prevalence rates. Interestingly these disorders are highly comorbid and show significant heritability, suggesting shared pathophysiological mechanisms. Non-homeostatic function of ion channels and neuroinflammation may be common mechanisms underlying both disorders: The excitation-inhibition balance of microcircuits and their modulation by monoaminergic systems, which depend on the expression and function of membrane located K+, Na+ and Ca+2 channels, have been reported to be disturbed in both depression and migraine. Ion channels and energy supply to synapses not only change excitability of neurons but can also mediate the induction and maintenance of inflammatory signaling implicated in the pathophysiology of both disorders. In this respect, Pannexin-1 and P2X7 large-pore ion channel receptors can induce inflammasome formation that triggers release of pro-inflammatory mediators from the cell. Here, the role of ion channels involved in the regulation of excitation-inhibition balance, synaptic energy homeostasis as well as inflammatory signaling in migraine and depression will be reviewed.